Hubungan Antara Green Accounting, Efisiensi Sumber Daya, dan Pelaporan Keberlanjutan Sustainability Management Accounting: Tinjauan Sistematis - Annisa Rahma Qur’aini; Reginata Saharany Kustanti; Via Wahyuningtyas; Dinata, Josephine Elliska; Maria Yovita R. Pandin (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The increasing global pressure for environmental sustainability has encouraged companies to adopt socially and ecologically responsible business practices. Green accounting has emerged as a strategic approach to integrate environmental information into corporate decision-making and reporting. This study aims to explore and analyze the relationship between green accounting, resource efficiency, and sustainability reporting within the framework of sustainability management accounting. The research employs a systematic review approach of 50 studies sourced from Google Scholar and the Wiley Online Library. The findings affirm that green accounting functions not only as an environmental recording system but also as a strategic management tool that supports operational efficiency and holistic sustainability reporting.